Wolne usta poety. Ethos słowa Józefa Wittlina - ZAJĄCZKOWSKI, Ryszard (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
The article focuses on the so-far uknown documents concerning Józef Wittlin which are stored in the Museum of Literature in Warsaw. Among them, are the notebooks Wittlin kept for over forty years. Their significance results from the fact that they provide a valuable commentary on his life and work, as well as shed light on his opinions on issues such as the social and political situation in Poland and Europe during the interwar period, literary life and America. Over a hundred and twenty notebooks include genuinely true and honest confessions of the writer, frequently made to himself, expressing his desire to articulate his views without subjecting them to any censorship or pressure. Thus Wittlin’s personal notes take on the proportions of an intimate diary, a special enclave of free word which he valued so highly. In the article, three important subjects which recur in Wittlin’s notebooks are considered, namely: religion, America and literary life. Throughout a period of a few decades, Wittlin experienced a spiritual evolution which resulted in his deepened and stronger religious beliefs. Being of Jewish nationality, he was exploring Christianity for decades and eventually came to the conviction that the Christian religion demonstrates a deep sensitivity to the value and dignity of a human person, together with the attitude of love which is due to human persons. His taking baptism, which he did at the age of fifty eight, was to him a challenge to adopt a thoroughly Gospel-based attitude in life. In 1941, Wittlin moved to America. One might say that he showed a European intellectual’s vision of that country in his notebooks. He would frequently compare the high, Mediterranean culture (the symbol of which was to him France) and its moral and aesthetic standards with the mass culture of America, which, in his opinion, did not exhibit a proper axiological dimension. He believed that as far as literature was concerned the main criterion of evaluation should be its originality, which he expected both of writers and of critics. He considered Witold Gombrowicz as an eminently original and non-humble writer, and admired him for his openness that allowed him to tell the Poles even most unpopular and harsh truths. Wittlin considered the work of Gombrowicz as tantamount with pursuit of inner freedom. The space of free word Wittlin’s notebooks reveal suggests that he belongs among the Polish masters of undertone such as Henryk Elzenberg, Karol Ludwik Koniński, Jan Lechoń, Jerzy Liebert, and Aleksander Wat. Translated by Dorota Chabrajska